Protective Behavioral Strategies and Alcohol Use Outcomes Among College Students: The Moderating Effects of Negative Affect. (March 2018) - Samuolis, Jessica; Loser, Ashley; Tyrrell, Amanda
The current study examined negative affect as a moderator of the relationships between protective behavioral strategies (PBS) used to reduce alcohol-related risk and alcohol use outcomes. Data were obtained from 267 college students using a web-based survey. The use of PBS (i.e., setting a limit on number of drinks, alternating drinks with water, avoiding drinking games) was associated with alcohol use and negative alcohol-related consequences. Negative affect symptoms moderated these relationships such that these relationships were stronger for those students who reported a greater number of negative affect symptoms. The findings indicate that the use of PBS by college students who consume alcohol are more protective for those with poorer mental health.